2001
DOI: 10.5194/npg-8-467-2001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to observations applied to FASTEX cases

Abstract: Abstract. The concept of targeted observations was implemented during field experiments such as FASTEX, NORPEX or WSRP in order to cope with some predictability problems. The techniques of targeting used at that moment (adjointbased or ensemble transform methods) lead to quite disappointing results: the efficiency of the additional observations deployed over sensitive areas did not turn out to remain consistent from one case to another. The influence of targeted observations on the forecasts could sometimes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…The development of the adjoint of the forecast model and of the adjoint of the data assimilation system (adjoint-DAS) makes feasible the evaluation of the derivative-based, local sensitivity (Cacuci, 2003) of a scalar forecast aspect with respect to a large number of DAS input components. Adjoint-DAS estimation of the observation sensitivity was considered in the work of Baker and Daley (2000) and Doerenbecher and Bergot (2001) as a tool to design observation targeting strategies. Subsequently, Langland and Baker (2004) have shown that the combined information derived from the adjoint of the forecast model and the adjoint-DAS may be used to provide a detailed (all-at-once) assessment of the observation impact on reducing the forecast errors in variational data assimilation (VDA).…”
Section: Introductionmentioning
confidence: 99%
“…The development of the adjoint of the forecast model and of the adjoint of the data assimilation system (adjoint-DAS) makes feasible the evaluation of the derivative-based, local sensitivity (Cacuci, 2003) of a scalar forecast aspect with respect to a large number of DAS input components. Adjoint-DAS estimation of the observation sensitivity was considered in the work of Baker and Daley (2000) and Doerenbecher and Bergot (2001) as a tool to design observation targeting strategies. Subsequently, Langland and Baker (2004) have shown that the combined information derived from the adjoint of the forecast model and the adjoint-DAS may be used to provide a detailed (all-at-once) assessment of the observation impact on reducing the forecast errors in variational data assimilation (VDA).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be noted that studies by Doerenbecher and Bergot (2001) and Fourrie et al (2002) use observation impact functions in observation space that are similar in form to Eq. (16) -e.g., they involve the innovation vector and an observation sensitivity gradient However, in those studies the observation sensitivity is not derived with an actual adjoint of the assimilation procedure.…”
Section: Observation Impact On Forecast Errormentioning
confidence: 99%
“…In data assimilation problems [1][2][3][6][7][8][9][10][11][12][13][14], usually, the cost functional (discrepancy between observations and model calculations) is minimized and assumes the following form:…”
Section: Problem Statementmentioning
confidence: 99%
“…In this approach, the forecast aspect gradients are estimated in metrics produced by the FIM resulting in a forecast aspect variance. The approach by Bergot and Doerenbecher [13,14] is very close to the V-optimality condition used in some works on the optimal experiment design [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation